(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines the strategies and practices to enhance the efficiency of enterprise warehouse activities in developing countries. It identifies the challenges faced by these enterprises in managing warehouse operations and explores effective solutions to overcome these obstacles. By analyzing various case studies and theoretical frameworks, the article provides insights into optimizing warehouse processes, leveraging technology, and implementing best practices to improve overall efficiency.